Administrative, conceptual aspects and clinical evaluation of the clinical maintenance phase, in the graduate courses of the Dental School, University of Antioquia. Administrative and conceptual aspects - Yepes-D., Fanny Lucía; Orozco-R., Luz Marina; Cabrales-M., Manuel (Revista Facultad de Odontología Universidad de Antioquia, 2018)
The purpose of this research was to fulfill an operative and conceptual evaluation of the clinical activities of the graduate courses of the Dental School of the Universidad of Antioquia. Like a contribution tu the educative and administrative context of the different graduate courses of the Irzstitution, they were also studied up to the point that cornmon processes to them were analized, such as the administrative and the academic-institutional conceptualization supports of the graduate courses, in relallon to the maintenance of the ended pacients for the effects of the udlity of these in teaching and research like an important part of the politics of clínica] formation of the stude.nt To recognize the thought of the different integrants of the school in relation with "rnaintenance phase" in the graduate courses, an survey was applied to the administrative-acadernic cupola of the institution thus like professors and students of the graduate courses, in order to know die degree of valuatiorz orimportance that each one ofthe integrates mentioned gives to the maintenance of the ended pacient like aneducative and administrative mode• the 625%, 46.2% and 61% respectively; considerated it "very important", however paradoxically there were not found guidelines or Tules that officiate the sistematic maintenance organization to cover the ended pacients, formirzg- a conceptual and pedagogicemptinessin the clinical teaching that contrasts with the academic aceptation oí" rnaintenance. That is so to say, yes" in teory, but no in application, in spite of the viabiliT to achieve it. The main reason with this study, is to emphasize the need of establishing the "maintenance" like a pennanentprocess in the school clinics.